REFORMA AGRARIA: MOMENTUM KEADILAN DAN KESEJAHTERAAN - Aprianto, Tri Chandra (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
At least there were two types of political events at the time of the implementation of agrarian reform in Indonesia, in both the process and practice. However, both events were not adequately used. As a result, the justice and welfare for poor Indonesian farmers were not yet fulfilled. The opportunity should be gained in order to implement the agrarian reform by the authoritative actor assisted by an institution various social sheltering social forces. Key words: agrarian reform, political momentum, agrarian justice